2017
DOI: 10.1021/acs.energyfuels.7b00573
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Improving Oil Recovery with Surfactant Additives to Completion Fluids for the Bakken

Abstract: Fracture treatment performance in Bakken liquid-rich shale reservoirs can be improved by altering rock wettability from oil-wet to water-wet. The use of surfactant additives for altering wettability also results in alteration of the interfacial tension (IFT). The Young−Laplace equation relates the capillary pressure to IFT and contact angle. Thus, it follows that capillarity is significant in nanopores associated with unconventional liquid reservoirs (ULRs) and complex as the contact angle (CA) and IFT varies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…The IFT values measured for single and mixed OPE surfactants with different EO chain lengths show that both single and mixed OPE solutions similarly have low IFT values and can effectively wet the rock surface, similar to previous results reported for ionic surfactants. ,,, However, the spontaneous imbibition results show that the oil recovery factor for single OPE solutions is not significantly different from the reference case without surfactants. In contrast, mixing OPE15 (oil-soluble with a short EO chain) with OPE70 (water-soluble with a long EO chain) leads to improved oil recovery from the oil-saturated tight core plugs.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The IFT values measured for single and mixed OPE surfactants with different EO chain lengths show that both single and mixed OPE solutions similarly have low IFT values and can effectively wet the rock surface, similar to previous results reported for ionic surfactants. ,,, However, the spontaneous imbibition results show that the oil recovery factor for single OPE solutions is not significantly different from the reference case without surfactants. In contrast, mixing OPE15 (oil-soluble with a short EO chain) with OPE70 (water-soluble with a long EO chain) leads to improved oil recovery from the oil-saturated tight core plugs.…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies ,, showed that synergistically favorable mixed nonionic–cationic and cationic–anionic surfactants can improve the oil recovery from tight carbonate rocks and shales, respectively. We studied the concept of mixing weakly interacting nonionic surfactants to enhance imbibition oil recovery from submicron pores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Alvarez et al showed that AS adsorption onto different Bakken shale samples has capacities ranging from 6.2 to 8.9 mg/g at 0.2 wt % concentration. 29 Missing in these studies is an understanding of how different shale components contribute to surfactant adsorption.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The distribution of different fluid phases in the pores affects rock/fluid properties including capillary pressure, waterflood behavior, relative permeability, and electrical characteristics of rock. Among the common techniques for evaluation of wettability (Anderson 1986), contact-angle measurement (Wang et al 2017), spontaneous imbibition (Dehghanpour et al 2012;Javaheri et al 2017), and nuclear magnetic resonance (Sulucarnain et al 2012) have been used for characterizing the wettability of tight and shale rocks with ultralow permeability.…”
Section: Introductionmentioning
confidence: 99%